Moringa oleifera prepared via supercritical fluid extraction as an alternative coagulant for water treatment / Muhammad Azroie Mohamed Yusoff - Muhammad Azroie, Mohamed Yusoff (2017)
The removal of turbidity is vital in water treatment plant operation, and is usually carried out by chemical coagulants e.g. aluminium sulphate (alum). In this study, supercritical fluid extraction (SFE) was used to prepare Moringa oleifera (M. oleifera) powder as a coagulant or bioflocculant for water treatment was studied. Relative to chemical coagulants, this bioflocculant will not cause adverse side effects towards human health and the environment. By using SFE, it can also eliminate hazardous chemicals that are used as solvents in the conventional extraction method. From 1 kg of raw M. oleifera, it produced 42% of pure M. oleifera powder, 30% of extracted oil and 28% of discarded husks. It was found that 0.01 g of M. oleifera coagulant was able to reduce more than 95% of turbidity and also reduced up to 60% in bacterial population in 1 litre of river water. In this study, we found that SFE could be used to produce coagulant from M. oleifera. The coagulant performed well and has the potential to replace alum as a main coagulant in water treatment plants. Sludge produced from these plants will be hazardous free and also will not fall in the category of scheduled waste.